Islamic Boarding School Culture Climate in Forming The Religious Attitude of Islamic Students in Modern and Agrobusiness Islamic Boarding Schools - Mahlil Nurul Ihsan; Nurwadjah Ahmad; Aan Hasanah; Andewi Suhartini (Nazhruna: Jurnal Pendidikan Islam, 2021)
The purpose of this study is to explain the Islamic Boarding School's cultural climate in shaping the religious attitudes of Islamic students at the modern Islamic Boarding School Al-Aqsho, Sumedang Regency, and Al-Ittifaq agribusiness Islamic Boarding School, Bandung Regency. The problem of this research begins with moral decadence and the decline in Islamic students' religious attitudes due to the influence of negative associations from outside the Islamic Boarding School and the lack of strengthening of the Islamic Boarding School's cultural climate. This study uses a qualitative field approach using descriptive analysis research methods with interview data collection techniques, documentation, and field observations. The results of this study indicate that the cultural climate of the modern Islamic Boarding School Al-Aqsho emphasizes the cultural climate of the modern system, while the Al-Ittifaq Islamic Boarding School in Bandung Regency emphasizes. Social culture, society, and agribusiness. Religious attitudes at the modern Islamic Boarding School Al-Aqsho are shown by the attitude of Islamic students who are obedient to worship, Islamic students who have moderate, balanced, open, and leadership attitudes, while the religious attitudes of Islamic students at Al-Ittifaq Islamic Boarding School display religious attitudes Islamic student who is socialist, hardworking, productive, useful and loves nature.